PERIODISMO Y AGENDA SETTING: UNA DISCUSIÓN SOBRE EL INTERÉS POR ASUNTOS PÚBLICOS DE LA CIUDADANÍA - Carazo Barrantes, Carolina (2018)
This article reflects on the ability of the media to set the citizens´ agenda for public discussion in the current context. It discusses the agenda setting theory and its thematic and temporal evolution over the last forty years and reflects on three specific issues: 1) the problematization of what a click means, 2) the need for orientation as an interest generator for public affairs and 3) citizens interest and their way of participating in politics today. The article presents examples of two presidential campaigns (2014 and 2018) in Costa Rica. In spite of the public’s preference for news on non-public affairs issues, the article also identifies clues that point to a citizenship with, at least, some degree of interest in public affairs.